Administrasi Perizinan Galian C di Nagari Buayan Kecamatan Batang Anai Kabupaten Padang Pariaman - Sriwahyuni, Rosi; Syamsir, Syamsir (PUBLICNESS: Journal of Public Administration Studies, 2023)
This study describes the administration of Excavation C permits in Nagari Buayan, Batang Anai District, Padang Pariaman Regency. It started with the C mining activity managed by PT Zulia Mentawai Rik which caused rejection from the community because the mining location was in a community plantation area. This study used a qualitative approach with descriptive methods supported by interview results. The data collection techniques for this research are observation, interviews, and documentation studies. The validity test was carried out using triangulation techniques, namely method triangulation and source triangulation. Data analysis techniques namely data reduction, data presentation, and drawing conclusions. The results showed that PT Zulia Mentawai Rik's Quarry C mining site, which is located in a community plantation area, is incompatible with Article 64 of Padang Pariaman Regency Regional Regulation Number 5 of 2020 concerning the RTRW of Padang Pariaman Regency for 2020-2040.